An Essay on the Principle of Population - Malthus, T. R. (Thomas Robert), 1766-1834 (Salt Lake City, UT : Project Gutenberg, 2003)
"An Essay on the Principle of Population" by T. R. Malthus is a book first published anonymously in 1798. It warns that population grows geometrically while food production increases arithmetically, inevitably leading to famine unless birth rates decrease. Malthus argued that population growth condemns segments of humanity to poverty, as societies expand during prosperous times until resources become insufficient. The work influenced both the census movement and Darwin's theory of natural selection. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/An_Essay_on_the_Principle_of_Population
Release date is 2003-07-01
Produced by Charles Aldarondo. HTML version by Al Haines.
Keywords: Population